Intrathoracic versus cervical anastomosis and predictors of anastomotic leakage after oesophagectomy for cancer. Issue 5 (7th February 2018) - Gooszen, J. A. H.; Goense, L.; Gisbertz, S. S.; Ruurda, J. P.; van Hillegersberg, R.; van Berge Henegouwen, M. I.
Abstract : Background: Studies comparing the anastomotic leak rate in patients with an intrathoracic versus a cervical anastomosis after oesophagectomy are equivocal. The aim of this study was to compare clinical outcome after oesophagectomy in patients with an intrathoracic or cervical anastomosis, and to identify predictors of anastomotic leakage in a nationwide audit. Methods: Between January 2011 and December 2015, all consecutive patients who underwent oesophagectomy for cancer were identified from the Dutch Upper Gastrointestinal Cancer Audit. For the comparison between an intrathoracic and cervical anastomosis, propensity score matching was used to adjust for potential confounders. Multivariable logistic regression modelling with backward stepwise selection was used to determine independent predictors of anastomotic leakage. Results: Some 3348 patients were included. After propensity score matching, 654 patients were included in both the cervical and intrathoracic anastomosis groups. An intrathoracic anastomosis was associated with a lower leak rate than a cervical anastomosis (17·0 versus 21·9 per cent; P = 0·025). The percentage of patients with recurrent nerve paresis was also lower (0·6 versus 7·0 per cent; P < 0·001) and an intrathoracic anastomosis was associated with a shorter median hospital stay (12 versus 14 days; P = 0·001). Multivariable analysis revealed that ASA fitness grade III or higher, chronic obstructive pulmonary disease, cardiac arrhythmia, diabetes mellitus and proximal oesophageal tumours were independent predictors of anastomotic leakage. Conclusion: An intrathoracic oesophagogastric anastomosis was associated with a lower anastomotic leak rate, lower rate of recurrent nerve paresis and a shorter hospital stay. Risk factors for anastomotic leak were co‐morbidities and proximal tumours. Abstract : Lower leak rates after intrathoracic anastomosis